The Influence of Petrography on the Relief of Bistriţei Mountains (The Eastern Carpathians) - Iulian SĂNDULACHE; Cătălina SĂNDULACHE; Alexandra RIZAC; Mihaela RAȘCU (Studia Universitatis Babeş-Bolyai: Geographia)
The Influence of Petrography on the Relief of the Bistriţei Mountains (The Eastern Carpathians). The petrographic characteristics impose certain general aspects in the morphology of any region. The geological composition of the Bistriţa Mountains is varied, being dominated by epimetamorphic rocks (sericitic, chlorite, graphite and quartzite schists) and mesometamorphic rocks (paragneisses, mica-schists, crystalline limestones and dolomites, amphibolites). To these, some isolated island-like areas of Mesozoic sedimentary rocks are added in the southern part, while in the eastern and southeastern parts, Cretaceous flysch, belonging to the Ceahlău Nappe is common. In the central axis there is a porphyroid dyke. From a geomorphological point of view, metamorphic rocks have encouraged the formation of dull, widely vaulted ridges, domes and deep valleys, with slopes having a convex profile. The porphyroid gneisses generated a relief of sharp, lofty ridges and peaks, with steep slopes. Long, narrow crests (called “obcine” in this area, too) and wide valleys develop on the sandy-shale flysch in the southeastern part. In the south, slender hills appear, due to the presence of dolomites and limestones, whose hardness exceeds that of the metamorphic rocks surrounding them. Levelled surfaces are very well preserved on the crystalline rocks. Where the valleys cut the Pietrosu gneiss bar or the epimetamorphic schists, gorges and defiles come into existence.